Digital Overload: Understanding Social Media Fatigue in Higher Education Based on Demographics and Technology Usage - Khairati, Annisaislami; Ifdil, Ifdil; Zulfi, Nur Adila Wafiqoh; Annisa, Dona Fitri; Putri, Yola Eka (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Social media has become an important part of students' lives in today's internet era, helping them meet their academic, social, and entertainment needs. However, excessive exposure to social media can cause fatigue, known as Social Media Fatigue (SMF), which affects students’ behavioural, cognitive, and emotional levels. This study aimed to analyse the level of social media fatigue based on demographics and technology access patterns. This research used a quantitative descriptive survey design with stratum random sampling technique by taking samples from various batches or years of student entry to the University. A total of 386 students participated, consisting of various batches or years of student entry (Year 2021 = 143 / 37.1%; 2022 = 97 / 25.1; 2023 = 80 / 20.7; 2024 = 66 / 17.1). The scale used in this study is the Social Media Fatigue scale (SMFS). Data were analysed using descriptive analysis with the help of JASP 0.19.3 software. The findings of this study indicated that the level of social media fatigue in students is high. Cognitive experience has the highest mean value among the three components of SMF, compared to emotional and behavioural experiences. In addition, findings suggested a tendency towards Emotional Experience, which may indicate that social media has a greater impact on their emotional well-being. Moreover, long access duration may worsen the consequences of social media fatigue.